AlFoCS + Fornax3D: resolved star formation in the Fornax cluster with ALMA and MUSE. Issue 2 (1st June 2020) - Zabel, N; Davis, T A; Sarzi, M; Nedelchev, Boris; Chevance, M; Kruijssen, J M Diederik; Iodice, E; Baes, M; Bendo, G J; Corsini, E Maria; De Looze, I; de Zeeuw, P Tim; et al.
ABSTRACT: We combine data from ALMA and MUSE to study the resolved (∼300 pc scale) star formation relation (star formation rate, SFR, versus molecular gas surface density) in cluster galaxies. Our sample consists of nine Fornax cluster galaxies, including spirals, ellipticals, and dwarfs, covering a stellar mass range of ∼10 8.8 –10 11 M⊙ . CO(1-0) and extinction corrected Hα were used as tracers for the molecular gas mass and SFR, respectively. We compare our results with Kennicutt and Bigiel et al. Furthermore, we create depletion time maps to reveal small-scale variations in individual galaxies. We explore these further in FCC290, using the 'uncertainty principle for star formation' (Kruijssen & Longmore) to estimate molecular cloud lifetimes, which we find to be short (<10 Myr) in this galaxy. Galaxy-averaged depletion times are compared with other parameters such as stellar mass and cluster-centric distance. We find that the star formation relation in the Fornax cluster is close to those from Kennicutt and Bigiel et al., but overlaps mostly with the shortest depletion times predicted by Bigiel et al. This slight decrease in depletion time is mostly driven by dwarf galaxies with disturbed molecular gas reservoirs close to the virial radius. In FCC90, a dwarf galaxy with a molecular gas tail, we find that depletion times are a factor ≳10 higher in its tail than in its stellar body.